Annual Plan 2000-2001 Government of Punjab - Planning Commission (Planning Commission, 2001)
The Planning Commission Govt. India has approved the size of the 9th plan (1997-2002) of the Punjab State at Rs. 14300.00 crores at current prices (Rs. 11500.00 crores at constant prices).An outlay of Rs. 2700.00 crores has been provided for the Annual Plan 2000-2001 against the previous year's outlay of Rs. 2680.00 crores. The major thrust area of the Annual Plan 2000-2001 would be diversification of Agriculture, Rural Development, Road and Bridges, Integrated Watershed Development (Hills), provision of qualitative education , better medical facilities and social seen/ices and upliftment of the weaker section of the society
Government of Punjab, Department of Planning